2022
DOI: 10.1186/s10194-021-01378-5
|View full text |Cite
|
Sign up to set email alerts
|

Monthly migraine days, tablet utilization, and quality of life associated with Rimegepant – post hoc results from an open label safety study (BHV3000–201)

Abstract: Background The objective of this study was to describe patterns in monthly migraine days (MMD) and tablet utilization, and to estimate health-related quality of life (HRQoL) measures in patients treated as needed (PRN) with rimegepant 75 mg over 52-weeks. Methods Eligible subjects were adults with ≥1 year history of migraine and ≥ 6 MMD at baseline, who used rimegepant 75 mg up to once daily PRN (at their discretion) for up to 52-weeks in an open-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…The most common side effects are nasopharyngitis, upper respiratory tract infection, sinusitis, and influenza. In this trial, three participants were pregnant during the intervention period, two of whom miscarried (Kudrow et al, 2021). This report is in line with the results of our meta-analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common side effects are nasopharyngitis, upper respiratory tract infection, sinusitis, and influenza. In this trial, three participants were pregnant during the intervention period, two of whom miscarried (Kudrow et al, 2021). This report is in line with the results of our meta-analysis.…”
Section: Discussionsupporting
confidence: 90%
“…A study shows that those with more frequent MMD have a lower quality of life, lower productivity, and a high burden of maintenance costs (Johnston et al, 2022). Our meta-analysis showed that the administration of eptinezumab decreased the mean MMD.…”
Section: Discussionmentioning
confidence: 58%
“…It would be difficult to modulate monoclonal antibody concentrations on a relevant time scale but this can readily be done for gepants. This is what the study of Johnston et al reports [ 15 ]. Modulation of CGRP blocking was instantiated by the need for taking 75 mg of rimegepant for acute treatment, and the authors’ analysis could show that this patient-determined practice is associated with a long-term reduction in monthly migraine days that seems to be of similar effect size as the overall preventive effect of 75 mg of rimegepant taken every other day (QOD) in the pivotal study by Croop et al [ 10 ].…”
Section: Main Textsupporting
confidence: 77%
“…In the USA, migraine is estimated to cost the economy US$19 billion a year. Each of the currently available CGRP-targeted mAbs and gepants have demonstrated improvement in functional and quality-of-life assessments (e.g., MIDAS, headache impact test (HIT-6), and health-related quality of life (HRQoL) [ 84 , 107 , 117 , 144 147 ].…”
Section: Expert Opinion For Use In Migraine Treatmentmentioning
confidence: 99%